Developing instrumental, transversal and vertical skills through transformative methodologies - Claudio Melacarne (Firenze University Press, 2019)
The article deals with the concept of capability and soft skills and how these competencies are becoming central for instructors and educators in formal and informal adult education settings. The article starts questioning how higher education classrooms can become a space to promote employability using collaborative development and action inquiry.   Supportare l'apprendimento di competenze strumentali, trasversali e verticali tramite metodi trasformativi L'articolo parte descrivendo la differenza tra capacità e competenze trasversali e di come queste stanno diventando centrali nel dibattito sull'innovazione dei sistemi di higher education e del rapporto tra formazione, mondo del lavoro e competenze sociali. Il contributo descrive come i setting formativi possono diventare uno spazio per promuovere l'occupabilità usando metodologie trasformative.